Cover Picture: Biotechnology Journal 2/2018. Issue 2 (2nd February 2018) - Unknown
Abstract : The work developed during the last decades in the research lab to develop genetic engineering tools for the generation and improvement of CAR T cells as a promising cell therapeutic option in the oncologic field is now reaching the clinic, opening new challenges for their large‐scale manufacturing. This is reported by Diogo Gomes‐Silva and Carlos A. Ramos, article number1700097 .